Perbedaan Hasil Belajar Siswa Melalui Penggunaan Metode Mind Mapping dan Metode Ceramah Pada Mata Pelajaran Pendidikan Agama Islam Di SMP Muhammadiyah 47 Sunggal - Muliana, Cut (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study aims to determine student learning outcomes in Islamic religious education subjects using the mind mapping method at SMA Muhammadiyah 47 Sunggal. How are student learning outcomes in Islamic education subjects with the lecture method, and what are the differences in student learning outcomes using the mind mapping method and using the lecture method at SMP Muhammadiyah 47 Sunggal. This type of research is a quantitative experiment with a quasi-experimental method. The research sample amounted to 35 class VII A for the experimental class, and for class VII B totaled 36 for the control class. The sampling technique is a Systematic Random sample. The instrument used in the study is in the form of an essay test that has been tested for validity, reliability and hypotheses. The results showed that the differences in student learning outcomes using the mind mapping method and the lecture method on Islamic education subjects in the experimental class could significantly affect student learning outcomes in Islamic education subjects. This can be seen from the average value of student learning outcomes in Islamic education subjects in the experimental class and the control class to get X1, X2 and Y =0,194 reliability. While the results of data analysis with r test obtained the value of rcount =1,51 So the calculation results show that rcount is more 0,75 than ttable (rcount3,89 ttable 1,28).